The Influence of the Big Five-Factor Personality Dimension on Employee Performance - Kasuma, Achmad Bintang Herida (International Journal of Applied and Advanced Multidisciplinary Research, 2024)
This study examines how personality traits, based on the Big Five model, impact job performance in business organizations. Through quantitative analysis, it finds that openness to experience and conscientiousness positively affect performance, while extraversion, agreeableness, and neuroticism show no significant influence. These results highlight the need to consider individual personality differences when managing employee performance. Recommendations include prioritizing openness to experience and conscientiousness in employee selection and development. Further research in varied contexts is advised to enhance the understanding of personality-performance relationships.